Climate Change and Sensitivity of Surface Water Resources in the Mekrou Sub-Watershed at the Yakrigourou Outlet (North Benin / West Africa) - AGUE, Alain Ibikunle; ETENE, CYR GERVAIS; PILABINA, Somiynbalo; Yabi, Ibouraïma (My University, 2021)
Tite prei;ent ,vork ainli to couuibute co a bener understai1ding of the ûnpac-rs of climace change 011 che availabihzy of ~,ufac~ ,vat~ re~ource~ w the :\,f~krou sub-basnl at the Yakt1gout'ou outle1 i.u n011hen1 Benin To ac.h1e,·e dus ObJ«tivc. dt'scripu,·e Mausuc.al method; \\"Cft applied ro hydro·cliru.atolog1cal data. The tustonc.tl data \Yt:re t.akt>u from the >1ccco-Belllll darabase and fr0t1l ilie Ge11eral Directorare of Water in Benin. The siruulatioll dara are those of the HadGE~12·ES clûnate ntodt"I undcr the RCP ..J 5 and RCP 8 5 toeitn.anœ and thcn at honzon~ 50 (2~1 to 2060) aud 70 (2061 to 2080) The rt-stùts sho,v thal the J)(riod froru 1965 to 2018 1s globally charactensed by a Mrong l1fegul1nry of 1.1ulfall \\'fth a dtcre.asu1g rrend .ind a multiplicat1011 of dry ye.ars es,irnated at 54°0. 111 the same ,vay. the n1noff decrease about S.S m1,s duting the decade 2007· 2016 L·ndet' the most pe~s1nuMic scen.ario (RCPS 5) and compared 10 the rer~ence penod (19Ïl·1990), the HadGEM2·ES model pre.dict.& au increase Ul annual precipitanon estuuated at S.~9°o by 204 l-2060 and 13.83°0 by ~061·2080. As regard& teruperature. there could be an increase of 1.4:-c by 20-11·2060 aJid 3.7"C by 2061-1080. These clituatic e,·e111s affecc die ;ava1lab1hty of ,i;urfuce ,vater rcsoutces in the \-u\>.ba\i:t1
Keywords: Clunate Ch.lngè; SenS.-Îtl\"lty; \Vater Rnourte\-; ~iekToU Sub-bas1n